Stock Market Optimality: Comment - LeRoy, Stephen F. (Quarterly Journal of Economics, 1976)
Journal Article Stock Market Optimality: Comment Get access Stephen F. LeRoy Stephen F. LeRoy Federal Reserve Board Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 90, Issue 1, February 1976, Pages 150–155, https://doi.org/10.2307/1886091 Published: 01 February 1976